(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: Nigeria faces a significant energy crisis characterized by a substantial gap between energy supply and demand, driven by rapid population growth, urbanization, and industrial expansion. With a projected electricity demand exceeding 50,000 MW by 2030, the country must explore underutilized resources to meet its energy needs. Non-Associated Gas (NAG) reservoirs present a viable solution, offering a cleaner and more stable fuel source than traditional fossil fuels. This paper examines the historical context of Nigeria's gas policies, highlighting key legislation such as the Petroleum Act, the Associated Gas Re-Injection Act, and the recent Petroleum Industry Act (PIA) of 2021. It discusses the challenges faced in gas utilization, including infrastructure deficits and investment barriers, while emphasizing the economic, environmental, and social benefits of developing NAG. The study also outlines recommendations for stakeholders to enhance investment in NAG infrastructure and create a favourable regulatory environment. By leveraging NAG, Nigeria can not only address its immediate energy crisis but also promote sustainable economic growth and improve energy security for its citizens.